Karakter Perakaran Sejumlah Varietas Kopi Arabika pada Fase Bibit di Pesemaian - Ari Wibowo (Agrotechnology Research Journal, 2021)
Roots represent the fundamental structure and material transport systems in plants. These important organs are used to study the adaptation processes in the environment. During the nursery stage, root evaluation serves as determining the seedling quality before transplant. This research aims to ascertain the root characteristics of several Arabica coffee varieties for a suitably vigorous root nursery system. Kaliwining Experimental Garden, Jember, Indonesia, served as the research location. The method used was a completely randomized design with a single factor, including arabica coffee varieties (Abesinia-3, Andungsari-1, BLP-4, Gayo-1, K-08, K-29, K-34, K-79, K-130, Kartika-1, Kayumas and Sigararutang). The result showed that the differences in the various sample factors significantly influenced the root properties. In addition, the entire observation parameters demonstrated a positive correlation except for the root and shoot ratio. Furthermore, BLP-4 v obtained the maximum values for plant height, stem diameter, fresh dry weight of taproot, and root biomass, while Gayo-1 variety observed the greatest number of leaves. Also, the Sigararutang variety indicated the highest value of the fresh and dry weight of shoot, fresh weight of lateral roots, and root length, while Kayumas and K-34 varieties acquired the lowest values of plant height, fresh and dry weight of shoot and root, as well as root length. Therefore, BLP-4, Gayo-1, and Sigararutang varieties exhibited the potentials of broader adaptability.